SARS-Corona Virus-2 Origin and Treatment, From Coffee to Coffee: A Double-Edged Sword - Reza Naghii, Mohammad (International Journal of Coronaviruses, 2020)
Identifying the epidemiological characteristics of COVID-19 disease will help to make appropriate decisions and thus control the epidemic. Although many details, such as the source of the virus and its ability to spread between people remain unknown, an increasing number of cases show the signs of human-to-human transmission. The purpose of this review is to introduce the reservoir hosts, and the possible role of distributions of bat coronaviruses in China, and eventually to aim to predict virus natural hotspots and their cross-species transmission potential. Why bats can maintain coronaviruses long-term without showing clinical symptoms of diseases and what is allowing bats to have a higher tolerance against viral diseases. We need to unveil the mystery of unique bat immunity. Although bats are not in close contact with humans, spillover of viruses from bats to intermediate animal hosts like civet is thought to be the most likely mode to cause human infection. It appears that the coffee beans which are a rich source of chlorogenic acid are acting as a reservoir host and causative agent, and at the same time as a defense agent to create resistance in the consumers (bats and animals). It is assumed that the intake of chlorogenic acid should be capable of protecting human from contamination or severe morbidity.
Keywords: SARS-Corona Virus-2; origin; treatment; coffee beans; bat; civet; chlorogenic acid